2013
DOI: 10.14453/aabfj.v7i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Working Capital Investment: A Study of Malaysian PublicListed Firms

Abstract: The paper examines the determinants of the level of investment in net operating working capital by firms in Malaysia. Data from 192 companies spanning a period of 8 years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) are analysed using the OLS regression technique for this purpose. The study finds that in times of economic expansion, younger and smaller firms with less tangible assets, low leverage, high immediate sales growth, high operating cash flows, less volatile revenues and low levels of asymmetric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
114
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(166 citation statements)
references
References 36 publications
32
114
3
8
Order By: Relevance
“…Other studies have examined the impact of various contextual factors on the value relevance of accounting information in various countries such as accounting practices in six Asian countries [23], investor protection in many countries [24], macro factors and bank-level factors in many countries [25], premium/discount firms in the United States [26], intellectual capital or intangible assets in Taiwan [27], improvements in working capital efficiency in Malaysia [3], financial crisis in Turkey [4], and adoption of international financial reporting standards (IFRS) in Norway [28], in Europe [29], in China [30], and in Indonesia [8].…”
Section: Value Relevance Of Financial Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined the impact of various contextual factors on the value relevance of accounting information in various countries such as accounting practices in six Asian countries [23], investor protection in many countries [24], macro factors and bank-level factors in many countries [25], premium/discount firms in the United States [26], intellectual capital or intangible assets in Taiwan [27], improvements in working capital efficiency in Malaysia [3], financial crisis in Turkey [4], and adoption of international financial reporting standards (IFRS) in Norway [28], in Europe [29], in China [30], and in Indonesia [8].…”
Section: Value Relevance Of Financial Statementsmentioning
confidence: 99%
“…Many previous studies have also examined and found factors affecting the relationship between accounting information and stock prices or stock returns. The factors include, for example, increased working capital efficiency [3], financial crises [4], sustainable cross-border cooperation [5], stakeholders' pressure [6], error occurrence in accounting [7], and presentation of financial statements based on International Financial Reporting Standards (IFRS) [8]. The current study examines whether the Sustainability Reporting Award (SRA) is a factor that affects the value relevance of accounting information.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive statistics shows different value of mean of cash for individual sectors. To find out whether this difference in means is statistically significant the study follows Wasiuzzaman and Arumugam (2013) and conduct a Non Parametric Kruskal-Wallis Test (Kruskal and Wallis, 1952). The results are shown in Table 2.…”
Section: Findings and Analysismentioning
confidence: 99%
“…Previous studies regarding working-capital management have examine the relationship between working capital and profitability (de Almeida, & Eid, 2014;Hill, Kelly, & Lockhart, 2012;Kieschnick, Laplante, & Moussawi, 2013;Knauer & Wohrmann, 2013;Tauringana & Afrifa, 2013;Wasiuzzaman, & Arumugam, 2013 Vol. 9, No.…”
Section: Review Of Working-capital Literaturementioning
confidence: 99%
“…However, firm managers focus on the largest components of current assets (accounts receivable and inventory) minus the largest component of current liabilities (accounts payable) to understand the cash flow needs of the firm (Knauer & Wohrmann, 2013;Rani, 2013). Previous research suggests efficient management of working capital affects profitability, and profitability affects firm value (de Almeida, & Eid, 2014;Hill, Kelly, & Lockhart, 2012;Kieschnick, Laplante, & Moussawi, 2013;Knauer & Wohrmann, 2013;Tauringana & Afrifa, 2013;Wasiuzzaman, & Arumugam, 2013). As each working-capital component (accounts receivable, inventory, and accounts payable) has a different effect on firm value, firm managers must be diligent in managing working capital optimally (Baños-Caballero, Garcia-Teruel, & Martinez-Solano, 2014;Aktas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%